Laparoscopic partial splenectomy by using two techniques in goats: Z. J. Malik1 and M. J. Eesa@2 - Eesa, Mohammad J. (The Iraqi Journal of Veterinary Medicine, 2015)
The aim of this study is to evaluate the laparoscopic partial splenectomy, using horizontal interrupted mattress suture and electro- cautery techniques in goats. Sixteenth adult goats were divided into two main equal groups (A and B). Each group was additionally divided into two equal subgroups, according to follow up on 15th and 30th days postoperatively for histopathology examination.All operations were performed under general anesthesia. Physical and clinical examination were measured pre-operatively and 1st to 7th days postoperative. The results revealed that the two techniques of both groups were performed successfully and the operation time in group A was 86.125±20 min., which was longer than that in group B 62.375±10 min. There were significant (P<0.05) differences in the physical parameters in all the experimental goats. All animals gradually returned to the normal solid food intake and activity, defecation and urination after 72hrs postoperative. Laparoscopic gross pathological changes revealed adhesions between spleen, rumen, and abdominal wall which were more severe in group A as compared with group B. Histopathology examination showed that both groups were associated with collagen and fibrous tissue formation similar to capsule surrounding the site of the incision, which was more in group B than in group A, and the latter group was infiltrated with more inflammatory cells. Also group B had more lymphocyte aggregation around the central artery, in addition to that there was thickness of capsule and mature granulation tissue, but in group A there was edema, congested red pulp and immature granulation tissue.